Analysis and experience summary of 64 cases of pediatric closed liver trauma: a retrospective study from two centers in China - Jie Liu; Wenli Xiu; Feifei Wang; Wenjie Bu; Guangyu Wang; Zhenjie Chu; Bao Wang; Ke Xu; Zihui Cheng; Nan Xia; Qian Dong; Aiqin Lin (BMC Surgery)
Abstract Backgroud Pediatric liver trauma is relatively common due to the liver’s large size, superficial location, and fragile tissue. Objective To investigate the clinical characteristics, diagnostic and treatment methods of pediatric closed liver trauma, and summarize treatment experiences. Methods A retrospective analysis was conducted on 64 pediatric patients with closed liver trauma admitted to Yijishan Hospital and Qingdao University Affiliated Hospital from May 2013 to July 2024. Diagnosis and treatment results were analyzed. Laboratory indicators (Hb, ALT, AST, m-AST, TBIL, PT, APTT) were compared before and after conservative therapy. Results The study included 39 males and 25 females. According to the AAST Liver Injury Grading Scale, there were 13 Grade I, 30 Grade II, 11 Grade III, 8 Grade IV, and 2 Grade V cases. 51 patients received non-surgical treatment, 11 had surgery due to hemodynamic instability, and 2 Grade V patients died from severe injury. All surviving patients were discharged after recovery with no bleeding or biliary stricture observed during follow-up. Significant differences were found in Hb, ALT, AST, m-AST, PT, and APTT before and after treatment in the non-surgical group (P < 0.05), while TBIL showed no significant difference (P = 0.102). In the surgical group, significant differences were found in Hb, ALT, AST, and m-AST (P < 0.05), but not in PT, APTT, and TBIL (P > 0.05). Logistic regression analysis indicated that Hb and m-AST at admission were independent predictors of surgical intervention. Conclusion Most Grade I and II, and some Grade III pediatric patients with stable hemodynamics can be treated non-surgically. Severe liver trauma (Grade IV and above) requires surgical intervention if hemodynamic instability occurs.